Protocol for hypofractionated adaptive radiotherapy to the bladder within a multicentre phase II randomised trial: radiotherapy planning and delivery guidance. Issue 5 (26th May 2020) - Hafeez, Shaista; Patel, Emma; Webster, Amanda; Warren-Oseni, Karole; Hansen, Vibeke; McNair, Helen; Miles, Elizabeth; Lewis, Rebecca; Hall, Emma; Huddart, Robert
Abstract : Introduction: Patients with muscle invasive bladder cancer (MIBC) who are unfit and unsuitable for standard radical treatment with cystectomy or daily radiotherapy present a large unmet clinical need. Untreated, they suffer high cancer specific mortality and risk significant disease-related local symptoms. Hypofractionated radiotherapy (delivering higher doses in fewer fractions/visits) is a potential treatment solution but could be compromised by the mobile nature of the bladder, resulting in target misses in a significant proportion of fractions. Adaptive 'plan of the day' image-guided radiotherapy delivery may improve the precision and accuracy of treatment. We aim to demonstrate within a randomised multicentre phase II trial feasibility of plan of the day hypofractionated bladder radiotherapy delivery with acceptable rates of toxicity. Methods and analysis: Patients with T2-T4aN0M0 MIBC receiving 36 Gy in 6-weekly fractions are randomised (1:1) between treatment delivered using a single-standard plan or adaptive radiotherapy using a library of three plans (small, medium and large). A cone beam CT taken prior to each treatment is used to visualise the anatomy and select the most appropriate plan depending on the bladder shape and size. A comprehensive radiotherapy quality assurance programme has been instituted to ensure standardisation of radiotherapy planning and delivery. The primary endpoint is to exclude > 30% acute grade > 3 non-genitourinary toxicity at 3 months for adaptive radiotherapy in patients who received > 1 fraction (p0=0.7, p1=0.9, α=0.05, β=0.2). Secondary endpoints include local disease control, symptom control, late toxicity, overall survival, patient-reported outcomes and proportion of fractions benefiting from adaptive planning. Target recruitment is 62 patients. Ethics and dissemination: The trial is approved by the London-Surrey Borders Research Ethics Committee (13/LO/1350). The results will be disseminated via peer-reviewed scientific journals, conference presentations and submission to regulatory authorities. Trial registration number: NCT01810757 .